Respiratory function test data and maximum oxygen consumption of children playing football in a hot and humid environment - BAZABA KAYILOU, Jean Michel; AHOUNOU AΪPE Judith; MOUKOUMBI MABIKA, Ghislain Aymard (Journal of Drug Delivery and Therapeutics, 2021)
Nowadays, the achievement of a good sporting performance depends on a good development of physical capacities from a young age while respecting the different stages of growth. In spite of this, some football coaches and trainers have no mastery of the principles of training. They subject children to physical effort that does not correspond to the child’s developmental stages. In order to evaluate the respiratory function and maximum oxygen consumption of children trained in football, series of test matches were organised by age group under a temperature of 38°C and a humidity of 60%. The results of the study show an increase in maximum oxygen consumption according to age with extremes of 36, 54 ml/min/kg and 55, 99 ml/min/kg. The classification of the values of V ̇O2max according to the spirometry values shows a representativeness of 13-14 year old children in the class of low spirometry values (CV, FEV1 and DEP) and a strong representativeness of 16-17 year old children in the class of high spirometry values (CV, FEV1 and DEP). A correlation exists between maximum oxygen consumption, spirometry equations and anthropometric parameters during the growth of children playing football. Keywords: Training, children, football, spirometry, Congo (Brazzaville)